An economic perspective on the environmental costs and benefits of irrigated agriculture - Wichelns, Dennis, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
A conceptual framework that depicts soma of the private and public costs and benefits of irrigated agriculture is presented for use in identifying situations in which public policies might be implemented to generate a socially optimal use of resources in a competitive equilibrium. The framework is useful in describing the potential social gains or losses due to policies that motivate farmers to internalize the external costs or benefits of their activities. The model is demonstrated using the example of water quality issues pertaining to irrigation and drainage in California's San Joaquin Valley. The potential social costs of public policies designed to reduce the volume of subsurface drain water and selenium loads discharged into the San Joaquin River are examined using the conceptual framework.
USCID 14th technical conference
Environmental costs and benefits
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.